THE EFFECT OF PERSON ORGANIZATION FIT AND PERSON JOB FIT ON TURNOVER INTENTION WITH WORK ENGAGEMENT AS MEDIATOR AT PT. TELEKOMUNIKASI INDONESIA REGIONAL I SUMATERA - Syarifah Hafni; Yeni Absah; Vivi Gusrini Rahmadani Pohan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
Human resources are currently very important for a company, where human resources are part of an asset but are intangible or intangible. In recent years, retaining employees in an organization has become very important, recruitment to find replacements for employees who have left starts from advertising costs in submitting job vacancies, interviews and selection, training costs for new employees and vacancy costs, which are situations where there is a vacancy. requires companies to look for employees to fill these positions.